Novel Insights Into Gene Signatures and Their Correlation With Immune Infiltration of Peripheral Blood Mononuclear Cells in Behcet’s Disease - Zhan, Haoting; Li, Haolong; Cheng, Linlin; Yan, Songxin; Zheng, Wenjie; Li, Yongzhe (Frontiers in Immunology, 2021)
Background: Behcet’s disease (BD) is a chronic inflammatory disease that involves systemic vasculitis and mainly manifests as oral and genital ulcers, ophthalmitis, and skin damage as the first clinical symptoms, leading to gastrointestinal, aortic, or even neural deterioration. There is an urgent need for effective gene signatures for BD’s early diagnosis and elucidation of its underlying etiology. Methods: We identified 82 differentially expressed genes (DEGs) in BD cases compared with healthy controls (HC) after combining two Gene Expression Omnibus datasets. We performed pathway analyses on these DEGs and constructed a gene co-expression network and its correlation with clinical traits. Hub genes were identified using a protein–protein interaction network. We manually selected CCL4 as a central hub gene, and gene-set enrichment and immune cell subset analyses were applied on patients in high- and low-CCL4 expression groups. Meanwhile, we validated the diagnostic value of hub genes in differentiating BD patients from HC in peripheral blood mononuclear cells using real-time PCR. Results: Twelve hub genes were identified, and we validated the upregulation of CCL4 and the downregulation of NPY2R mRNA expression. Higher expression of CCL4 was accompanied by larger fractions of CD8 + T cells, natural killer cells, M1 macrophages, and activated mast cells. Receiver operator characteristic curves showed good discrimination between cases and controls based on the expression of these genes. Conclusion: CCL4 and NPY2R could be diagnostic biomarkers for BD that reveal inflammatory status and predict vascular involvement in BD, respectively.